Synthesis, characterization, and performance evaluation of novel stabilized TDI-based polyurethane coatings under accelerated weathering - Kumar, A. P.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Raut, K. G.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2005)
Some toluene dilsocyanate (TDI)-based polyurethane resins (PURs) for coating applications were synthesized with castor oil and their performance was estimated under accelerated UV weathering with and without a novel UV absorber. Changes in physical properties, chemical structure, and color of the samples were monitored by mechanical property testing, FTIR spectroscopy, and colorimetry, respectively. A stable polyurethane coating was achieved at 0.5% concentration of additive in the host matrix. Mechanical properties were also retained as in the pristine PUR after mixing. Commercial Tinuvin P and benzotriazole-based novel UV absorbers were found to improve the photoresistance of the PUR coating, and the highest efficiency of the novel UV absorber against weathering was estimated at 0.5 wt% concentration.(c) 2005 Society of Plastics Engineers.

Synthesis, characterization, and performance evaluation of polymeric HALS in ethylene-propylene-diene terpolymer (EPDM) - Lonkar, Sunil P.; Rana, S.; Singh, R. P.; Lacoste, Jacques; Gardette, Jean Luc; Jestin, F.; Brocord, E. (Journal of Macromolecular Science, Part A: Pure and Applied Chemistry, 2005)
A polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the maleic anhydride graft ethylene-propylene-diene terpolymer (EPDM) was synthesized. This involves photoinduced grafting of maleic anhydride groups on unsaturated sites of EPDM, followed by incorporation of amino terminated HALS. The grafting and functionalization reactions were characterized by FTIR and C-13 NMR spectroscopy. The surface changes upon degradation are studied by SEM. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The HALS grafted EPDM showed significantly improved photostabilizing efficiency.
Keywords: EPDM; light induced grafting; Photostabilization; polymeric HALS

Self photostabilizing UV-durable MWCNT/polymer nanocomposites - Lonkar, Sunil P.; Kushwaha, Omkar S.; Leuteritz, Andreas; Heinrich, Gert; Singh, R. P. (RSC Advances, 2012)
A potentially active hindered amine light stabilizer (HALS) was successfully anchored onto multiwalled carbon nanotubes (MWCNTs) and used as a light-stabilizing yet reinforcing multifunctional nanofiller to obtain UV-durable polymer nanocomposites. The influence of such light stabilizing MWCNTs on the photo-oxidation behaviour and structure-properties of polypropylene (PP) was studied. The composites were prepared by solution mixing of MWCNTs followed by melt compounding with polypropylene (PP). The resulting composite exhibits excellent UV-durability showing an almost 20 fold increase in the induction period of photo-oxidation. Moreover, the hydrophobic HALS was found to be compatibilizing enough to achieve homogeneous dispersion of exfoliated nanotubes into a polymer matrix. The rheological characterizations predict the formation of a percolated network structure. The obtained nanocomposites present markedly improved mechanical properties which underline the reinforcing ability of functionalized MWCNTs. Overall combination of HALS and MWCNTs offers an attractive route to combine multifunctionality into new hybrid UV-durable polymer nanocomposites. Such materials may possess great potential for outdoors high performance applications.

Synthesis and characterization of a new diol-functionalized s-triazine-based polymerizable hindered amine light stabilizer - Mehare, Rupali S.; Lonkar, Sunil P.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2012)
A new diol-functionalized triazine-based polymerizable hindered amine light stabilizer (HALS) was synthesized in two steps. First, selective synthesis of an s-triazine containing two HALS moieties as substituents was accomplished by using phase-transfer catalysis. This step required the establishment of optimum reaction conditions (type of two-phase system, best solvent, and catalyst). In the second step, the substituted triazine was treated with diethanolamine to introduce polymerizable diol functionality. The resulting product should act as a light stabilizer, since it contains two HALS moieties anchored to a thermally stable s-triazine unit. Moreover, incorporation of the diol into a polymeric material might be expected to impart prolonged stability in weathering environments. Characterization of the diol was accomplished by using Fourier transform infrared spectroscopy (FTIR), `H NMR, and mass spectrometry. J. VINYL ADDIT. TECHNOL., 18:204208, 2012. (c) 2012 Society of Plastics Engineers